Hydrogen sulphide alleviates depression-like behaviors by suppressing the hippocampal necroptosis-neuroinflammation-KP imbalance axis - Yang, San-Qiao; Tang, Yu-Hui; Chen, Si-Min; Liu, Fen; Zhang, Ping; Zou, Wei; Wang, Bo; Tang, Xiao-Qing (Frontiers in Pharmacology, 2025)
BackgroundWe have previously demonstrated that hydrogen sulfide (H2S) is sufficient to attenuate depressive-like behavior induced by chronic unpredictable mild stress (CUMS), but its underlying mechanisms remain largely unknown. It is well known that necroptosis is a trigger of inflammation and neuroinflammation-induced kynurenine pathway (KP) imbalance is the main pathogenesis of depression. Meanwhile, H2S plays a pivotal role in the inhibition of inflammatory pathways. Hence, the present study sought to investigate whether the antidepressant effect of H2S is attributable to the inhibition of the axis of hippocampal necroptosis-neuroinflammation-KP imbalance.MethodsThe depression model of Sprague-Dawley (SD) rats was established by CUMS for four consecutive weeks. The expressions of necroptosis-related protein and KP-related protein were evaluated by Western blotting (WB). The levels of inflammatory factors were measured by enzyme-linked immunosorbent assay (ELISA). The hippocampal metabolites of tryptophan were determined by LC-MS/MS.ResultsIn this study, we found that H2S was capable of inhibiting necroptosis and neuroinflammation and correcting KP imbalance in the hippocampus of CUMS-exposed rats. The enhancement of necroptosis via overexpressing RIPK3 reversed the antagonistic role of H2S in the depressive-like behaviors of CUMS-exposed rats and the inhibitory effects of H2S on necroptosis, neuroinflammation, and KP imbalance in the hippocampus of CUMS-exposed rats. Furthermore, overexpressing indoleamine 2,3-dioxygenase 1 (IDO1) abolished the correcting effect of H2S on hippocampal KP imbalance and the attenuating effect of H2S on depressive-like behaviors in the CUMS-exposed rats.ConclusionThe antidepressant-like role of H2S is achieved by negatively regulating the axis of necroptosis-neuroinflammation-KP imbalance in the hippocampus.